MEASURING DRIVERS OF PROCRASTINATION IN ACADEMIC STUDENT - Dzarr Alghifari Wijanarko, Abi
Procrastination is the lack or absence of self-regulated performance and the tendency to deny or completely avoid an activity under one’s control (Tuckman & Sexton, 1989). MARS, also known as model of individual behavior, are model used to understand on what drivers can form an individual behavior. It consist of four factors which are motivation, ability, role perceptions, and support/situational factors).As an organization, academic institution need to know the drivers of behavior that might affect their academic members performance, including student. This research aims to identify the level of procrastination in SBM ITB as an academic organization, finds correlation between MARS model and procrastination level, and identify the most dominant factor from MARS model that contributes to procrastination level. By creating a Procrastination Scale to measure procrastination level and Academic Motivation Scale into MARS model this research gather a 116 sample of academic student that at least in the third year of study in SBM ITB. Using Pearson correlation analysis, the result shows that Amotivation (r=.212) and Motivation External of external regulation (r=.202) has positive correlation with procrastination level. Using hierarchical regression analysis, the result further show that amotivation (b=.197) act as the most dominant contributor to procrastination level. External Motivation of external regulation (b=.126) follows as the second contributor while Situational Factors (b=-.127) shows as counter contributer of procrastination. Since Amotivation, External Motivation of external regulation and Situational Factors finds to be as the dominant contributive factors, there are several further steps SBM ITB could take. SBM ITB might want to further motivate their student and give tutoring about managing academic and non-academic activities. SBM ITB might also want to maintain their support to students to avoid further problem about increasing procrastination level. Other correlative factors such as Perceived Ability that correlate positively with procrastination, also gives insight that students need to be given challenging enough tasks and proportional time allocation of deadline.